Answer:
Step-by-step explanation:
Answer:
A. 0.623
Step-by-step explanation:
Hope it helps you in your learning process.
Equation 1) x + 6y = 2
Equation 2) 5x + 4y = 36
Multiply all of equation 1 by 5.
1) 5(x + 6y = 2)
Simplify.
1) 5x + 30y = 10
2) 5x + 4y = 36
Subtract equations from one another.
26y = -26
Divide both sides by 26.
y = -1
Plug in -1 for y in the first equation.
x + 6y = 2
x + 6(-1) = 2
Simplify.
x - 6 = 2
Add 6 to both sides.
x = 8
D : (8, -1)
~Hope I helped!~
Answer:
x - ![\frac{10}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B7%7D)
Step-by-step explanation:
y = x + 10/7
x = y + 10/7
x = y + 10/7
x - 10/7 = y
y = x - 10/7
x - ![\frac{10}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B7%7D)
Answer:
-3
Step-by-step explanation:
First step to this is to replace the variables with their coordinated values. Remember to use parentheses.
4(2)-2(2+4)+1=?
We can start to simplify.
4(2)-2(6)+1
Then---
8-12+1
-4+1
Final Answer (-3)